The Hexahelix Collaboration Model for Stunting Prevention: A Case Study of Collaborative Governance in Rancakalong, Sumedang - Cece Mulyadi; Bintarsih Sekarningrum; Deni Kurniadi Sunjaya; R. Anang Muftiadi (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2026)
Background: Child stunting remains a critical global health and development issue with profound long-term consequences.Aims: This study aims to analyze the application of the hexahelix collaboration model in the stunting prevention program in Rancakalong District, Sumedang Regency, Indonesia.Methods: A qualitative case study approach was used to identify and analyze six key helices: Government, Community, Private Sector, Academics, Media, and Policy. The research examines the roles, contributions, and interactions of these six actors within a single, integrated framework to address the multi-causal nature of stunting.Results: The analysis reveals a novel conceptualization of Policy as a distinct, foundational helix that acts as the primary governance structure. Findings show that a layered, synchronized policy framework from the national to the village level facilitates the integration of diverse stakeholder efforts. The collaboration leverages technological innovation (e.g., the SIMPATI application), community-based action rooted in local wisdom, strategic private-sector partnerships, and evidence-based input from academia. The media's role in public education and social accountability further strengthens the model's effectiveness. Data indicates a significant decrease in stunting prevalence in Rancakalong from 27.61% in 2017 to 7.59% in 2025.Conclusion: These findings demonstrate that a well-defined policy helix can mitigate common challenges in multi-actor interventions. The hexahelix model provides a replicable empirical framework for tackling complex public health issues in developing contexts.